Health financing in Ghana, South Africa and Nigeria: Are they meeting the Abuja target? - Rachael S. Burke; Devi Lalita Sridhar (University of Oxford, Global Economic Governance Programme (GEG), 2013)
This paper uses budgetary documents from African health and finance ministries to assess the extent to which African governments are meeting targets set at the Organisation for African Unity Summit, held in Abuja in 2001. Drawing on three case studies (Ghana, Nigeria and South Africa), the authors explore how public healthcare systems are organised; how countries allocate domestic and foreign resources; and whether governments are complying with the Abuja target of spending 15% of government income to achieve health-related Millennium Development Goals, goals for universal coverage of basic healthcare, health equity goals, and financial risk protection. Whilst recognising that this figure is not straightforward to calculate - due to substantial discrepancies in health spending data between national ministries of finance, the WHO, the World Bank and the OECD - the paper argues that South Africa largely meets the Abuja target, whereas Ghana and Nigeria fall short. The paper strongly recommends that the Abuja target may not be the most effective way to improve public health.
Keywords: 330